Effect of Byrsocarpus Coccineus (Connaraceae) Aqueous Leaf Extract on Pancreatic Islets Volume in Type 2 Diabetic Male Wistar Rats. (Nigerian Journal of Physiological Sciences, 2019)
Diabetes mellitus is a devastating illness associated with alterations in the pancreatic islet of Langerhans and the islet volume constitutes a significant variable in diabetic investigations. This study investigates the volume of pancreatic islets in type 2 diabetic rats following treatment with aqueous extract Byrsocarpus coccineus leaves. Twenty-five male Wistar rats weighing between 100-120g were divided into five groups. Group 1 served as the normal control given distilled water while type 2 diabetes mellitus was induced by a high fat diet feeding for five weeks and a single dose of streptozotocin (35mg/kg, i.p.) in groups 2,3,4 and 5. After confirmation of diabetes, animals in groups 2,3,4 and 5 were administered normal saline, 50 mg/kg metformin, 800 mg/kg Byrsocarpus coccineus leaves leaf extract (BCLE) and 400 mg/kg BCLE respectively for 21 days. The pancreas was harvested, fixed in neutral buffered formalin and processed for stereological and histological analysis. Isotropic uniform random samples were obtained with the orientator grid. Serial sections were cut with a rotatory microtome and stained with Haematoxylin and Eosin. Pancreatic islet volumes were measured with the aid of a Cavalieri estimator grid. The result showed significant (p